Empreendedorismo ético e solidário: desafios e potencialidades - Saraiva, Rosana Lucille Bassinello (2013)
This Doctor's Thesis aims to examine the possibility of undertaking ethics and solidarity in the view of the Science of Anthroposophy. In this paper the reader will become familiar with this social issue through a vast bibliographical review of the Science of Anthroposophy, based on the works of its pioneer, Rudolf Steiner, and other anthroposophers who follow his ideas. In addition, other authors here are presented as they also relate to this social issue, but who have convergent ideas from the ones found in Anthroposophy. Furthermore, a case study is presented, which was conducted by the Community Association of Monte Azul, a socially responsible organization that has its foundation on the Science of Anthroposophy. This is to provide relevant facts of this biography organizational, with emphasis on the action of the founder of this social work, Ute Craemer Else Ludovic, as well as a documentary analysis of Participatory Planning, from 2009 to 2013, with all the social and community programs of this Association, spread over three different cores covered: Monte Azul, Peinha and Horizonte Azul, and also with exposure to the vision of the future and the objectives of each program. For the composition of the case study, a research was conducted with two groups of respondents, both from Monte Azul Community Association: strategic group, of goals, and leadership group or support, of coordinators. The findings from the data allowed for a categorical thematic analysis, which shows the indicators of research for each question, as well as the correlation of indicators into categories, and also comments from the analysis. As a result, it was observed that both the ethical issue and the issue of solidarity are referenced by the attitudes and behaviors described in the case study, in the interviewees' testemonials. The conclusion is done by means of a reflection on the initial problematic proposal